Garçons manqués and femmes fortes: Two ambivalent figures of butch lesbianism in women's football in Cameroon - Ndjio, Basile (African Studies Review, 2022)
With the enactment of anti-homosexuality laws in the 1960s, Cameroon's government officially endorsed heterosexualist ideologies which legitimize the alienation and criminalization of minority and nonconforming sexual and gender identities. One group, the so-called garçons manqués, embodies the stigmatized masculine or "butch" lesbian identity. The political management of lesbianism in Cameroon is ambivalent, however, with respect to sport, and particularly regarding the national pastime, football. Whereas masculine lesbians are routinely branded as "butches" or "sexual predators" who threaten African hetero-patriarchy, "strong women"" (femmes fortes) are celebrated as pivotal to the national ambition. Cameroon's government strategically amalgamates both heteronationalism and homonationalism in the interest of national pride.
Keywords: afrique; anthropologie; approches et analyses; butch; cameroun; discipline; discours dominant; hétérosexisme; personnes lesbiennes; ressource en ligne; régions géographiques; sciences humaines; sexisme; sport; systèmes d'oppressions

Empowerment as a disabled, black woman - Oliver, Kym; Abdullahi, Jumoke (2020)
The dynamic duo of Jumoke and Kym tackle the topic of empowerment and what that means for disabled, Black women. This was filmed as part of a TEDx talk at the University of Sussex in England. _______________________________________________________________________________________________ TRIPLE CRIPPLES was created by @TheKymOliver & @JayOnLife to provide a platform for & highlight the narratives of Black & non-Black Women, Femmes & Non-Binary people of colour, living with disabilities. We are here. We exist! We know the media and mainstream disability conversations would have you believe otherwise mega eye roll*... But guess what? WE GOTS THA INTERNETS, BITCHEZZZZ!!! Eat it. *put on shades and look cool at night ———————————————————————————————- JOIN US ON OUR JOURNEY! Hit the comments box! And if you or any women/femmes/non-binary people you know, would like to be a guest... Hit the DM’s! 🖤 Website: https://thetriplecripples.uk/ Twitter/Instagram: @TripleCripples Follow Jumoke: @JayOnLife Follow Kym: @TheKymOliver ———————————————————————————————- Track: “runaway” ~ K15 feat. AMA LIVE! Big Love to K15 for kindly letting us use his amazing music as our bedding track!!! Check out @k15music, support his sound, buy some vinyls and follow him on all platforms: Twitter: @K15music Facebook: @K15music Soundcloud: @K15 Bandcamp: @K15music
Keywords: 2000 à aujourd'hui; afrique; amériques; approches et analyses; capacitisme; caraïbes; corps; cours; discours dominant; empowerment; europe; fem3300; femmes* noires; invisibilité; militance; premier cycle; périodes historiques; ressource en ligne; royaume-uni; régions géographiques; systèmes d'oppressions; thématiques